2008
DOI: 10.1097/brs.0b013e31816245c0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Neutralization of the Lumbar Spine After Microsurgical Decompression in Acquired Lumbar Spinal Stenosis and Segmental Instability

Abstract: The reported biomechanical principles of Dynesys do not reflect advantages in outcome compared with none or others stabilization systems after microsurgical radicular decompression reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 29 publications
1
66
0
5
Order By: Relevance
“…Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20]. At present, several clinical reports have demonstrated that Dynesys implantation does not induce a problem in the adjacent facet joint [2][3][4][5][6][7]. Therefore, the present study deems that Dynesys resulted in a lower incidence of adjacent facet degeneration than did the rigid fixation system.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20]. At present, several clinical reports have demonstrated that Dynesys implantation does not induce a problem in the adjacent facet joint [2][3][4][5][6][7]. Therefore, the present study deems that Dynesys resulted in a lower incidence of adjacent facet degeneration than did the rigid fixation system.…”
Section: Discussionmentioning
confidence: 47%
“…The location of high screw stress in FE analysis was different from the location of screw breakage in a previous clinical report [7]. One possible reason may be the modelling of the bone-screw interface and consideration of the screw thread.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations